1998
DOI: 10.1002/(sici)1097-0282(199610)39:4<491::aid-bip2>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Carboxyl-terminal peptides from histone H1 variants: DNA binding characteristics and solution conformation

Abstract: The carboxyl‐terminal domains of the histone H1 proteins bind to DNA and are important in condensation of DNA. Little is known about the details of the interactions between H1 histones and DNA, and in particular, there is little known about differences among variant H1 histones in their interactions with DNA. Questions concerning H1 histone‐DNA affinity and H1 conformation were investigated using peptide fragments from the carboxyl terminal domains of four nonallelic histone H1 variant proteins (mouse H1‐1, H1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…This implies that the tendency for aggregation is caused by the nature of the entire C-terminal domain. It has been shown that the C-terminal domain of H1 histone is involved in the formation of higher order chromatin structures (36) by binding to DNA and by interaction with other H1 molecules (37,38). Therefore, it may be that intermolecular interactions of the C-terminal domain or binding to nucleic acids may cause the observed aggregation.…”
Section: Fig 5 Mapping Of the Imp␤ Binding Domain In Imp7supporting
confidence: 68%
“…This implies that the tendency for aggregation is caused by the nature of the entire C-terminal domain. It has been shown that the C-terminal domain of H1 histone is involved in the formation of higher order chromatin structures (36) by binding to DNA and by interaction with other H1 molecules (37,38). Therefore, it may be that intermolecular interactions of the C-terminal domain or binding to nucleic acids may cause the observed aggregation.…”
Section: Fig 5 Mapping Of the Imp␤ Binding Domain In Imp7supporting
confidence: 68%
“…This region may contribute to the DNA-binding activity of Xbp1 and could possibly compensate for the missing HTH motif found in the other family members, since this carboxy-terminal domain of the histone H1 variants is sufficient to bind DNA and efficiently condense chromatin (21,58). This latter property may also provide a clue to the mechanism by which Xbp1 represses transcription.…”
Section: Discussionmentioning
confidence: 99%
“…Recent results have indicated that the C-terminal domains of H1 proteins are primarily responsible for their DNA-binding properties (74), and it has been shown that synthetic peptides from the C-terminal domain of different H1 isoforms, including H1°, do not differ in their affinity for DNA (75). Recent experiments using H1-green fluorescent protein fusion proteins and photobleaching techniques have indicated a continuous and rapid exchange of H1 molecules in living cells (76,77).…”
Section: Discussionmentioning
confidence: 99%